ARCHITECTURAL DEVELOPMENT OF SACRAL SPACE OF CITY OF KHARKOV - , О. О. (Municipal economy of cities. Series: «Economy science», 2017)
Sacral space of city is intercommunicated multilevel system that created toponimy of urban landscape the aggregate of working templates and design of street-art (muraliens) and structure of city monuments and statues. Those components determine of unique qualities of city image and in constant virility. Sacral space of city of Kharkov is variable now in the end of XX century and demands of clear determination. Thus, spatial development sacred image developed through further development: - Church nodes Orthodox temples; - Construction monuments, monuments of national heritage and design; - Street art by major urban thoroughfares and historic environment. This multilevel structure of sacred imagery will create new synthetic spatial image of the city. Keywords: space of city, design, street-art, toponimy, urban landscape